Kolaborasi Sekolah dan Industri: Menyiapkan Siswa Untuk Dunia Kerja - Fadya Safitri Rahman; Agilia Febriani; Fadillah Annisak; Irlyanova Sabina; Pramudia Ananda (Pusat Riset dan Inovasi Nasional, 2024)
In order to face challenges in the industrial sector and strengthen entrepreneurial culture, collaboration between schools and the business world/industrial world is really needed. Provisions related to business and industrial activities are not only carried out in special or vocational schools, but can be provided from elementary school. The research method used in this article is qualitative. The results of the analysis show that collaboration between schools and industry in preparing students for the world of work is a form of technological and vocational education innovation in Indonesia which expects schools and industry to play a greater role in determining, encouraging and driving technology education and students must be able to understand both theoretical and practical by applying it directly to the world of work.